Co(ii) coordination polymers constructed from a bent chiral linker: influencing framework topology using co-ligands. Issue 40 (23rd September 2020) - Tay, Hui Min; Hua, Carol
Abstract : The reaction of a semi-rigid chiral ligand with Co(ii ) and dipyridyl co-ligands of varying length yielded a series of 2D coordination frameworks, with the topology of the network mediated by the length of the co-ligands. Abstract : A semi-rigid chiral ligand (1 R, 2 R )-4, 4′-( trans -cyclohexane-1, 2-diyl)bis(azanediyl)bis(carbonyl) dibenzoic acid (H2 cbba) was combined with various Co(ii ) salts and dipyridyl co-ligands to obtain four 2D homochiral coordination polymers of composition [Co(cbba)(dipyridyl)]·solvate (dipyridyl = 4, 4′-bipyridyl (bipy), bis(4-pyridyl)ethylene (bpe), 1, 4-bis(4-pyridyl)benzene (1, 4-bpb), 2, 5-bis(4-pyridyl)thiazolo [5, 4- d ]thiazole (2, 5-bptztz)) (1–4 ). The topology of the frameworks is mediated by the length of the co-ligands, with short dipyridyl co-ligands (4, 4′-bipy and bpe) resulting in the formation of (4 13 ·6 2 ) networks (1–2 ), while long co-ligands (1, 4-bpb and 2, 5-bptztz) led instead to (4 4 ·6 2 ) (sql) networks that undergo 2D → 2D parallel interpenetration to form a rare example of a homochiral polyrotaxane (3–4 ). The length of the dipyridyl co-ligand was also found to have an effect on the conformation of the flexible cbba 2− ligands and the crystal packing of the networks.